Factors affecting the use of accounting information in small and medium enterprises (SMEs): a study on SMEs in Tingkir, Salatiga - Maria Entina Puspita; Joko Pramono (STIE Perbanas Surabaya, 2019)
This study aims to examine the effect of business turnover, business’ age, educational level, accounting knowledge, accounting training and owner motivation on the use of accounting information in Small and Medium Enterprises (SMEs) in Tingkir, Salatiga City. The data were collected using accidental sampling where the respondents were SMEs who were willing as the respondents for this research. This study used primary data in the form of questionnaires for 30 respondents. This is an explanatory study with a quantitative approach to explain the relationship between variables by testing hypotheses and conducting statistical tests. Data were analyzed using multiple linear regression. The results showed that only accounting training was statistically proven to have a positive effect on the use of accounting information for SMEs in Tingkir Salatiga. Other variables such as business turnover, business’ age, educational level, accounting knowledge and motivation were not statistically proven to have an effect on the use of accounting information in these SMEs.